2021
DOI: 10.3390/healthcare9121690
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving Role and Psychosocial and Individual Factors: A Systematic Review

Abstract: Taking care of a person with a physical disability can become a challenge for caregivers as they must combine the task of caring with their personal and daily needs. The aim of this study was to assess the impact that taking care of a person who needs support has on caregivers and to analyze certain characteristics they present, such as self-esteem and resilience. To that end, a bibliographic review was carried out from 1985, when the first article of taking care of a person who needs support was published, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 81 publications
(213 reference statements)
1
8
0
1
Order By: Relevance
“…Specifically, we confirmed that lower resilience levels predicted higher levels of individual distress during the lockdown, as reported in our previous study [ 31 ], as well as in other studies conducted among the general population [ 45 , 46 ]. Our results are consistent with past literature reporting that higher levels of resilience are associated with lower levels of distress in family caregivers [ 47 ]. Resilience can be defined as the capacity for successful adaptation in front of adversities and can be determined by either individual, family, or community factors [ 48 ].…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, we confirmed that lower resilience levels predicted higher levels of individual distress during the lockdown, as reported in our previous study [ 31 ], as well as in other studies conducted among the general population [ 45 , 46 ]. Our results are consistent with past literature reporting that higher levels of resilience are associated with lower levels of distress in family caregivers [ 47 ]. Resilience can be defined as the capacity for successful adaptation in front of adversities and can be determined by either individual, family, or community factors [ 48 ].…”
Section: Discussionsupporting
confidence: 93%
“…In some cases, the unemployment of the patient and the caregiver aggravates these problems (Given et al, 2012 ). More importantly, the lack of social support and the unnecessary stringent measures of insurance companies in releasing the payments for medical expenses might make the burden even greater (Cejalvo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Resilience has been proven to be a protective factor for adaptation and against stress and burden among caregivers (Cejalvo et al, 2021 ; Palacio et al, 2020 ). Teaching caregivers how to develop a resilient style is considered a necessary subject in intervention programs.…”
Section: Discussionmentioning
confidence: 99%